Synthesis, Structure, and Anticancer Activity of a Dinuclear Organoplatinum(IV) Complex Stabilized by Adenine - Alisha M. O’Brien; Kraig A. Wheeler; William A. Howard (Compounds, 2025)
The dinuclear platinum(IV) compound {Pt(CH3)3}2(μ-I)2(μ-adenine) (abbreviated Pt2ad), obtained by treating cubic [PtIV(CH3)3(μ3-I)]4 with two equivalents of adenine, was isolated and structurally characterized by single crystal X-ray diffraction. The National Cancer Institute Developmental Therapeutics Program’s in vitro sulforhodamine B assays showed Pt2ad to be particularly cytotoxic against the central nervous system cancer cell line SF-539, and the human renal carcinoma cell line RXF-393. Furthermore, Pt2ad displayed some degree of cytotoxicity against non-small cell lung cancer (NCI-H522), colon cancer (HCC-2998, HCT-116, HT29, and SW-620), melanoma (LOX-IMVI, Malme-3M, M14, MDA-MB-435, SK-MEL-28, and UACC-62), ovarian cancer (OVCAR-5), renal carcinoma (A498), and triple negative breast cancer (BT-549, MDA-MB-231, and MDA-MB-468) cells. Although anticancer studies involving some adenine platinum(II) compounds have been reported, this study marks the first assessment of the anticancer activity of an adenine platinum(IV) complex.